Pengaruh Model Pembelajaran Team Games Tournament (TGT) Terhadap Minat Belajar Pendidikan Agama Kristen Dan Budi Pekerti Siswa Kelas IV Di SD Negeri 3 Pasar Pangururan Tahun Pembelajaran 2023/2024. - Christ August Trinity P; Johari Manik; Frainskoy Rio Naibaho (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
The research aims to determine the influence of the Team Games Tournament (TGT) learning model on interest in studying Christian Religious Education and Characteristics of class IV students at SD Negeri 3 Pasar Pangururan for the 2023/2024 academic year. The research hypothesis is that there is a positive influence between the Team Games Tournament (TGT) learning model on interest in studying Christian Religious Education and Characteristics of class IV students at SD Negeri 3 Pasar Pangururan for the 2023/2024 academic year Quantitative and descriptive research methods. The population of all class IV students at SD Negeri 3 Pasar Pangururan for the 2023/2024 academic year who are Protestant Christians is 60 people. This research is population research. The research instrument is a closed questionnaire. The results of data analysis obtained: a) The value of rcount=0.583>rtable=0.254 shows that there is a positive influence between the Team Games Tournament (TGT) learning model and students' interest in learning Christian Religious Education and Character. b) Regression equation. c) The determination test revealed that the magnitude of the effect was 33.99%. d) Hypothesis testing obtained Fcount=29.896>Ftable=3.15 so H0 is rejected and Ha is accepted. The research concluded that there was a positive influence between the Team Games Tournament (TGT) learning model on interest in studying Christian Religious Education and Characteristics of class IV students at SD Negeri 3 Pasar Pangururan for the 2023/2024 Academic Year.